The Nature of Actin-Family Proteins in Chromatin-Modifying Complexes - Klages-Mundt, Naeh L.; Kumar, Ashok; Zhang, Yuexuan; Kapoor, Prabodh; Shen, Xuetong (Frontiers in Genetics, 2018)
Actin is not only one of the most abundant proteins in eukaryotic cells, but also one of the most versatile. In addition to its familiar involvement in enabling contraction and establishing cellular motility and scaffolding in the cytosol, actin has well-documented roles in a variety of processes within the confines of the nucleus, such as transcriptional regulation and DNA repair. Interestingly, monomeric actin as well as actin-related proteins (Arps) are found as stoichiometric subunits of a variety of chromatin remodeling complexes and histone acetyltransferases, raising the question of precisely what roles they serve in these contexts. Actin and Arps are present in unique combinations in chromatin modifiers, helping to establish structural integrity of the complex and enabling a wide range of functions, such as recruiting the complex to nucleosomes to facilitate chromatin remodeling and promoting ATPase activity of the catalytic subunit. Actin and Arps are also thought to help modulate chromatin dynamics and maintain higher-order chromatin structure. Moreover, the presence of actin and Arps in several chromatin modifiers is necessary for promoting genomic integrity and an effective DNA damage response. In this review, we discuss the involvement of actin and Arps in these nuclear complexes that control chromatin remodeling and histone modifications, while also considering avenues for future study to further shed light on their functional importance.